Conocimiento y aceptación del programa habla serio, sexualidad sin misterios del Ministerio de Salud Pública en los estudiantes del Colegio Juan Montalvo de la ciudad de Loja del periodo académico 2013-2014 - Cisneros Galindo, Gustavo Patricio (2014)
The study labeled "Knowledge and acceptance of the program ¡Habla serio, sexualidad sin Misterios! of the Ministry of Public Health, in the students of Juan Montalvo High school of Loja city” is analytic, quantitative and qualitative, cross-sectional; conducted on a sample of 85 students, during the period December 2013 to March 2014. The objective was to: determine the knowledge of the students about the program “Habla serio, sexualidad sin misterios” (Speaks Seriously, sexuality without mysteries), the topics that includes, and the level of acceptance that produces this program on students. The determination of these data was performed by applying a survey technique, with the following results: Of all respondents, 50.6% were male and 50.4% female, being the most prevalent age range of 16 to 18 years with 80%. The largest capacity of advertising about the program to the students was television with 74.1%, 63.5% of students have superficial knowledge about the program, 44.7% of respondents received little sex education during the primary, 63.5% have insufficient knowledge about STIs, 80% have not used condoms dispensers of Ministry of Public Health, 76.6% say that is positive delivering free condoms, 95.3% consider favor the inclusion of sex education in educational institutions, 63.6% do not know their sexual rights. In conclusion, more than half of the respondents have surface knowledge of the program “Habla serio, sexualidad sin misterios”, and its thematics showing gaps in broadcasting issues, which exposes them to commit recklessness in the practice of his sexual life, affect their long-term human, social and economic development. Most considered positive the approaches of this program and believe that should be incorporated into their academic plan. So this study will promote the inclusion of the program “Habla serio, sexualidad sin misterios” in educational institutions. Keywords: Adolescents, sex education, family planning.